Marjolin's ulcer--a near forgotten entity - Tan, B.C.; Horton, T.C.; Ahmad, T.S. (Malaysian Medical Association, 2006)
We report a case of a 55-year-old man who presented with a 6-month history of a fungating ulcer on the right hand at the site of a previously healed ulcer that had been present for 40 years. Histopathological examination of four-quadrant biopsy specimens showed a moderately differentiated squamous cell carcinoma (SCC). A transradiocarpal amputation with stump closure using radial flap was performed as it was not possible to achieve a functionally and cosmetically acceptable hand after a wide excision with 2 cm tumour-free margin. It is our intention to highlight this rare condition as reminder to consider this entity as a differential diagnosis of chronic non-healing skin ulcer.